Triple receptor-positive primary neuroendocrine carcinoma of breast in a young patient - Vats, Manu (BMJ Case Rep, 2018)
Primary neuroendocrine carcinoma of breast is a very rare malignancy and preoperative diagnosis is difficult by clinical examination alone. Most oftenly, histopathological examination (HPE) and immunohistochemistry (IHC) studies are required to establish the diagnosis. We describe here a case of a primary neuroendocrine carcinoma of right breast in a 32-year-old woman. The patient underwent a right modified radical mastectomy, and the diagnosis was conclusively established postoperatively by the HPE and IHC reports. The IHC report revealed positive status of oestrogen, progesterone and Herceptin receptors.